Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.31235/osf.io/p3z9v
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Systematic Review of Worldwide Causal and Correlational Evidence on Digital Media and Democracy

Abstract: One of today's most controversial and consequential questions is whether the rapid, worldwide uptake of digital media is causally related to a decline in democracy. We conducted a systematic review of causal and correlational evidence (N=498 articles) on the link between digital media and different political variables, such as trust, polarization or news consumption. We further focused on the subset of articles that employed causal inference methods. Across methods, the articles report associations between dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 118 publications
2
9
0
Order By: Relevance
“…For example, the introduction of 3G in the United States increased Democrats' liberal leanings and Republicans' conservative leanings (Melnikov, 2021). A systematic review of digital media's relationship with democracy around the world found that most studies find detrimental associations between digital-media use and political polarization (Lorenz-Spreen et al, 2021). This is consistent with other research showing that the introduction of mobile Internet reduces national identification by 5% to 7% by exposing people to greater polarization online (Choi et al, 2021).…”
Section: -314)supporting
confidence: 72%
See 1 more Smart Citation
“…For example, the introduction of 3G in the United States increased Democrats' liberal leanings and Republicans' conservative leanings (Melnikov, 2021). A systematic review of digital media's relationship with democracy around the world found that most studies find detrimental associations between digital-media use and political polarization (Lorenz-Spreen et al, 2021). This is consistent with other research showing that the introduction of mobile Internet reduces national identification by 5% to 7% by exposing people to greater polarization online (Choi et al, 2021).…”
Section: -314)supporting
confidence: 72%
“…Pan, 2017). And just as technological features can support authoritarian control from the top down, they may also influence key political outcomes such as populism and far-right voting from the bottom up (Lorenz-Spreen et al, 2021). Thus, although this article examined the influence of recent technological developments on the freedom of the individual, our work has obvious implications for freedom at the societal level.…”
Section: Discussionmentioning
confidence: 97%
“…At the level of institutions, the structures of public institutions (e.g., government [1] and social and mass media [61][62][63][64][65]) may amplify stereotypes, making each side seem like a caricature of itself by incentivizing provocative and outrageous rhetoric. These institutions are the platforms for public dialogue, and norms tilt towards hostility.…”
Section: What Causes Partisan Animosity?mentioning
confidence: 99%
“…However, a growing body of literature suggests a different picture. Despite a homophilic structure of online social networks, the exposure to cross-cutting content is, by far, no exception in online environments (Bakshy et al, 2015;Barberá et al, 2015;Bright et al, 2020;Lorenz-Spreen et al, 2021;Oswald & Bright, 2022;Vaccari & Valeriani, 2018) and most users continue to receive political information from their favorite, mostly mainstream, news outlets (Flaxman et al, 2016;Guess, 2021;. It is, of course, difficult to define a benchmark of an 'ideal level' of opinion heterogeneity or 'ideal' diversity in news consumption.…”
Section: Political Engagement Onlinementioning
confidence: 99%